Penerapan whistleblowing system pada partai politik sebagai upaya pencegahan tindak pidana korupsi (Komisi Pemberantasan Korupsi, 2023)
Political parties are an important element of democracy. Ethical standards, accountability, and the culture of party democracy all require attention. This study examines the implementation of a whistleblowing system in political parties and its effectiveness in preventing corruption. The data was obtained through interviews and observations were processed into formulating descriptive solutions. The outcome is a system developed by the authorial team called SIAPP (Political Party Information and Complaint System). SIAPP is a digital platform owned by political parties containing information about anti-corruption work and education schemes, interactive community access, and information surrounding complaints. The SIAPP can support the implementation of the Political Party Integrity System Module (SIPP) launched by the KPK RI. Political parties need to be transparent so that the public knows of anti-corruption work schemes, ethical standards for party cadres, and the culture of party democracy. The study results state that political parties and anti-corruption activists agree with the SIAPP mechanism offered because it is felt to be quite effective in preventing political corruption and could encourage party transparency to gain public trust.